Cortical thickness in bipolar disorder: a systematic review. (6th February 2016) - Hanford, Lindsay C; Nazarov, Anthony; Hall, Geoffrey B; Sassi, Roberto B
Abstract : Objectives: Bipolar disorder (BD) is a debilitating illness, the psychopathology of which is associated with aberrant structural and functional differences in the brain. Despite the many advances in psychiatric research, our understanding of the complex neurobiological underpinnings of BD remains incomplete. The aim of this review was to critically examine all available published magnetic resonance imaging (MRI) research reporting cortical thickness in BD with respect to a healthy population and/or other psychiatric samples. Methods: The systematic search encompassed all relevant studies published until November 2014. Relevant papers were identified through an online search of select databases (MEDLINE and EMBASE) using key terms bipolar disorder or mania, and cortical thickness . Two independent raters determined the eligibility of papers and performed separate data extraction to ensure quality and accuracy of reporting. Results: A total of 17 papers met the criteria and were included in this review. Compared to a healthy population, the majority of studies reported decreased cortical thickness in the left anterior cingulate/paracingulate and the left superior temporal gyrus, as well as several prefrontal regions bilaterally in patients with BD. Studies also show consistency of cortical thinning in individuals with BD and schizophrenia in frontal and temporal regions, suggesting some common neuropathology. Conclusions: This systematic review further supports a link between specific structural brain abnormalities and BD. Future studies should investigate cortical thickness with respect to at‐risk populations to determine whether these neuropathologies develop before or after the onset of BD.